SCAPULAR DYSKINESIS AND WORK-RELATED PAIN IN OFFICE WORKERS: A CROSS-SECTIONAL STUDY (Journal of Medical & Health Sciences Review, 2025)
Background: Office workers, particularly those working with computers for prolonged hours, were at high risk of developing scapular dyskinesia due to repetitive work and poor posture. Investigation was needed to determine how often scapular dyskinesia occurred in office workers, its association with pain, and the intensity of pain experienced.Objective: The study aimed to determine the prevalence of scapular dyskinesia and examine its association with work-related pain among office workers.Methodology: This cross-sectional study was conducted among office workers aged 20–50 years in Karachi, Pakistan, who worked at least 6 hours daily. Convenience sampling selected 140 participants (70 males, 70 females). The Lateral Scapular Slide Test (LSST) assessed scapular dyskinesia, and pain intensity was measured using the Visual Analog Scale (VAS). Data were analyzed using SPSS version 26. Chi-square tests evaluated associations, with significance at p ≤ 0.05.Results: Of 140 participants, 72 (51.43%) exhibited scapular asymmetry, while 68 (48.57%) had balanced scapulae. The age group 26–30 years had the highest scapular asymmetry prevalence (58.3%). Gender distribution of asymmetry was 52.7% males and 47.2% females. Pain levels showed 14 (10%) reported no pain, 85 (60.7%) mild pain, 37 (26.4%) moderate pain, and 4 (2.9%) severe pain. Moderate and severe pain were most common in the 26–30 age group (51.2%). Chi-square tests showed significant associations between scapular dyskinesia and work-related pain, except for age-pain intensity and gender-scapular stability relations.Conclusion: Scapular dyskinesia was common among office workers and significantly associated with work-related pain. Early ergonomic interventions and physiotherapy could reduce scapular asymmetry and pain, improving office workers' health and productivity.